THE ROLE OF THE DEPARTMENT OF SOCIAL AFFAIRS IN THE IMPLEMENTATION OF REGIONAL REGULATION NUMBER 15 OF 2004 CONCERNING THE PROHIBITION OF VAGRANCY AND BEGGING IN TANJUNG BALAI CITY FROM THE PERSPECTIVE OF SIYASAH DUSTURIYAH - Nabila Sandu Br Sinaga; Muhibbussabry Muhibbussabry (Journal Analytica Islamica, 2025)
This study discusses the implementation of Tanjung Balai City Regional Regulation Number 15 of 2004 concerning the Prohibition of Vagrancy and Begging from the perspective of Siyasah Dusturiyah. The phenomenon of the increasing number of vagrants and beggars (gepeng) in Tanjung Balai City indicates a gap between the ideality of law (das sollen) and social reality (das sein). The purpose of this study is to analyze the effectiveness of the implementation of the regulation, to identify its inhibiting and supporting factors, and to assess its conformity with the principles of public benefit (maslahah) in Siyasah Dusturiyah. This research employs an empirical juridical approach with a qualitative descriptive method through interviews, observations, and document studies. The results show that the implementation of the regulation remains weak due to budget limitations, insufficient rehabilitation facilities, and lack of inter-agency coordination. Moreover, the legal substance of the regulation focuses more on control and sanctions without being balanced by rehabilitation and social empowerment policies. From the perspective of Siyasah Dusturiyah, such a policy has not fully fulfilled the principles of maslahah ‘ammah and maqasid al-shariah, as it has not yet succeeded in ensuring protection, empowerment, and justice for the poor. This study concludes that the handling of vagrancy and begging should be directed toward economic empowerment, moral guidance, and social reintegration based on Islamic values so that regional social policies genuinely reflect public welfare and human dignity.